Development of a Learning Management Model Using a Cooperative Learning Management Approach to Promote Critical Thinking for Students of the Faculty of Education, Uttaradit Rajabhat University - Ounraun, Walida (Journal of Education Studies, Chulalongkorn University, 2025)
The purposes of this study were to: 1) create and evaluate the effectiveness of learning management models, and 2) study the results of using these learning management. The sample consisted of 40 students from the Faculty of Education, Uttaradit Rajabhat University acquired by cluster sampling. Tools used to collect information are critical thinking tests. The statistics used for data analysis included mean, standard deviation, content analysis, and one-sample t-test. The results of the research showed that: 1) The developed model includes the learning management model included five components: 1) principles 2) objectives 3) content 4) teaching and learning activities which included five teaching steps namely: learning management planning, teaching, cooperative learning group activities, performance review and testing, and lesson summary and group work evaluation and 5) measurement and evaluation. The results of the model evaluation and the model guide were appropriate. The performance evaluation result of the model equals to 77.04/77.78, in accordance with the set criteria, and 2) after study, the sample has the mean score of analytical thinking higher than before study at the .05 level of statistical significance. Students displayed appropriate analytical thinking and were able to participate in group process activities using effective cooperative learning management approaches.